Datafication and the Development of Global Digital Civilizations (Glocalism: Journal of Culture, Politics and Innovation, 2019)
New emerging technologies and the continuous process of digitisation around the globe means a new model of civilization is emerging where society is “digitized” or “datafied”. This paper analyses to what extent we have undergone the process of digitisation and datafication through understanding concepts of the surveillance society, spectacle society, our digital footprints and the amount of data gathered by government agencies, individuals and companies and its utilisation; and how this process has led to the development of a “global digital civilization”. Disparity between levels of digitisation in different regions in a globalised world are addressed to determine if certain regions contend hegemony over others within digital realms. To further understand how globalisation itself is perceived in a digitised world, a software called “Mention” was used to collate data in relation to the terms “globalization”, “global” and “globalisation” on digital platforms such as Twitter, blogs, news, websites and forums over a month’s time period. Online rhetoric in relation to this term and the locations from which data was mostly surfacing in higher amounts has greatly added to the findings.
Keywords: datafication; global digital; digitisation; digital civilization; digital citizen